Encyclopedia of school psychology - Lee, Steven W. (Steven Wayne), 1951- (Gale virtual reference library., 2005)
Comprehensive guide to the field of school psychology featuring the latest research on school learning, motivation, and educational assessment. Entries on psychology, education and counseling, child development, and special education address student success, behavior disorders, intelligence testing, learning disabilities, strategies to improve academic skills, and more.